2018
DOI: 10.14740/cr749w
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of the Left Circumflex Artery With Super-Dominant Right Coronary Artery: Extremely Rare Coronary Anomaly

Abstract: Among the congenital anomalies of the coronary arteries, absent left circumflex artery (LCX) defect is extremely rare. Only a few cases have been reported in the literature. We report a case of a 48-year-old female who presented with a 4-month history of exertional chest pain with positive stress (treadmill) test. Conventional coronary angiogram showed a normal left anterior descending, absent LCX and a super-dominant right coronary artery (RCA) with prominent branches. Aortography also failed to show a separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In those cases who had myocardial infarction secondary to acute thrombotic occlusion of the superdominant RCA, results in a large infarction of the inferior, posterior and lateral walls, which were stated to be similar to two-vessel disease involving both RCA and LCX simultaneously. 17,40,52 In all CALCx cases, STEMI was by far the most common clinical manifestation as an acute coronary syndrome and the second most prevalent clinical diagnosis in our case series.…”
Section: Coronary Artery Disease and Calcxmentioning
confidence: 73%
“…In those cases who had myocardial infarction secondary to acute thrombotic occlusion of the superdominant RCA, results in a large infarction of the inferior, posterior and lateral walls, which were stated to be similar to two-vessel disease involving both RCA and LCX simultaneously. 17,40,52 In all CALCx cases, STEMI was by far the most common clinical manifestation as an acute coronary syndrome and the second most prevalent clinical diagnosis in our case series.…”
Section: Coronary Artery Disease and Calcxmentioning
confidence: 73%
“…The previously published reports described patients who underwent angiography for exertional chest discomfort and were found to have either high-grade stenosis in a dominant RCA [3] or no significant coronary stenosis [4]. We have also found few reports of congenitally absent LCX and super-dominant RCA but with normal LAD origin which might carry similar clinical significance and further emphasize on the importance of precise morphological and functional evaluation of the CAA in selecting the best treatment modality and better prognosis [5-8].…”
Section: Discussionmentioning
confidence: 89%
“…Its possible variations have been well documented. In rare cases, it could be absent congenitally, in which case, the right coronary artery is super dominant [1]. A recent study from Thailand by Kultida et al (2018) [4] has reported the absence of the left main coronary artery and left circumflex artery in 0.4% cases.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary arteries are the branches of ascending aorta and they supply the myocardium of the heart. Some of the variations like, absence of one of the coronary arteries [1], origin from pulmonary trunk [2], and origin of both coronary arteries as a common trunk [3] have been reported in the literature. The anatomical variations may or may not affect the normal functioning of the heart.…”
Section: Introductionmentioning
confidence: 99%